Penguatan Pengetahuan Remaja Tentang Bahaya Rokok Melalui Penyuluhan Digital Berbasis Powerpoint - Sheinni Paradise; Yuri Pratiwi Utami (Institut Kesehatan Suaka Insan, 2026)
Background: Adolescents are a vulnerable group to smoking behavior, while their knowledge about the dangers of smoking remains low. Objective: This community service activity aimed to strengthen adolescents’ knowledge about the dangers of smoking through digital counseling using PowerPoint. Methods: The counseling was delivered directly using PowerPoint media containing visual and informative materials, accompanied by discussion sessions and pre- and post-counseling knowledge evaluations. Results: Wilcoxon analysis showed a significant increase in knowledge between pre-test and post-test (p = 0.000), with 26 participants improving, 4 participants unchanged, and none declining. Conclusion: Digital counseling using PowerPoint is effective as a health education medium in community service activities because it systematically improves adolescents’ knowledge about the dangers of smoking in an engaging and easily understood manner.